Videogrammetric reconstruction applied to volcanology: perspectives for a new measurement technique in volcano monitoring - Cecchi, Emmanuelle (Image analysis and stereology, 2002)
This article deals with videogrammetric reconstruction of volcanic structures.As a first step, the method is tested in laboratory. The objective is to reconstruct small sand and plaster cones, analogous to volcanoes, that deform with time. The initial stage consists in modelling the sensor (internalparameters) and calculating its orientation and position in space, using a multi-view calibration method. In practice two sets of views are taken: a first one around a calibration target and a second one around the studied object. Both sets are combined in the calibration software to simultaneously compute the internal parameters modelling the sensor, and the external parameters giving the spatial location of each view around the cone. Following this first stage, a N-view reconstruction process is carried out. The principle is as follows: an initial 3D model of the cone is created and then iteratively deformed to fit the real object. The deformation of the meshed model is based on a texture coherence criterion. At present, this reconstruction method and its precision are being validated at laboratory scale. The objective will be then to follow analogue model deformation with time using successive reconstructions. In the future, the method will be applied to real volcanic structures. Modifications of the initial code will certainly be required, however excellent reconstruction accuracy, valuable simplicity and flexibility of the technique are expected, compared to classic stereophotogrammetric techniques used in volcanology.
Keywords: Fotogrametrija; Volcanic Eruption; Image Processing, Computer-Assisted; Slika, obdelava z računalnikom; Video Recording; Video snemanje; Photogrammetry; Vulkanski izbruh; videogrametrija; vulkani; modeli